Chronic diseases among women of reproductive age in primary care: prevalence and associated factors - Débora Cristina Martins; Giordana Maronezzi da Silva; Beatriz Maria dos Santos Santiago Ribeiro; Elen Ferraz Teston; Michele de Paula Pavan; Carlos Alexandre Molena Fernandes (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To analyze the prevalence and associated factors with chronic diseases among women of reproductive age in primary health care. Method: Cross-sectional study conducted with 397 women of reproductive age living in northern Paraná, Brazil. Data were collected from July 2019 to September 2020. The Women's Clinical Record was used to collect sociodemographic data, risk behaviors, diagnosis of chronic diseases and medication use. Chi-Square test was performed for association analysis, and Logistic Regression estimating Odds Ratio and 95% confidence intervals. Results: The prevalence of chronic diseases among women of reproductive age was 38.53% and the associated factors were: age group from 31 to 40 years old (OR=3.67; p=0.001) and from 41 to 49 years (OR =9.7; p=0.001), incomplete high school education (OR= 2.7; p=0.001), obesity (OR= 2.25; p=0.001) and smoking (OR=2.23; p=0.001). Conclusion: Age at the end of the reproductive phase, obesity and smoking were associated with the presence of chronic diseases. Knowledge of these factors can assist in screening, monitoring and health education actions provided to women of childbearing age.